An Overview of Geography and Biodiversity in the Himalayan Region - Mahendra Singh; Ishrat Mohd; Santosh Kumar; M.S. Akhter; Jyoti Upadhyay; Shivani Pathak (Journal of Indian Fisheries Association, 2024)
The Himalayan region is a geologically dynamic and ecologically rich mountain system,spanning diverse climate zones and altitudes. Its unique geography supports a wide range of ecosystems, from tropical forests to alpine meadows, and harbors significant biodiversity, including endemic cold-water fish like Schizothorax spp. and Tor putitora. However, climate change, glacial retreat, habitat degradation, and invasive species threaten both ecological balance and local livelihoods. This review highlights the interlinked geographical and biological features of the Himalayas and emphasizes the need for integrated conservation and sustainable management strategies